The dragon and the horn: reflections on China–Africa strategic relations - Ylönen, A. (Insight on Africa, 2020)
Historically, China maintained relations with faraway lands. These links included the intercontinental Silk Road and maritime trade routes, which connected China with other continents, including the eastern shores of Africa. However, apart from the exchange of goods, these routes also had a globalising effect through the spread of cultural influences, technology, ideologies and philosophical thought. Following its new push into Africa in the 1990s, China sought to rebuild these connections and has gone further to exert its influence through the Belt and Road Initiative. This article analyses China’s renewed interest in Africa, which increasingly ties the continent to the Indian Ocean economic area. It also reflects on some of the economic effects of Chinese involvement on the continent. The article shows that China initially sought to ensure access to strategic resources but has later moved to safeguard its growing involvement by establishing a physical and increasingly permanent presence in the territories of its key partners. While maintaining a selection of these partners at the core of its Africa policy, the Chinese economic engagement will continue to bring further economic benefits for the collaborating elites and their states. However, ensuring sustained growth and economic equality requires China’s key partners to engage in sound economic planning, policies and management.